Membangun Pendidikan Islam yang Berdaya Saing: Analisis Kesenjangan dan Solusi - Aji Swasono, Pangestu (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the quality gap in Islamic education in Indonesia, particularly in terms of curriculum, access to education, and the utilization of technology. It employs a library research method by reviewing academic literature sourced from reputable national and international journals, scholarly books, and research reports from relevant educational institutions, accessed through databases such as Google Scholar, ScienceDirect, and Garuda. The data analysis technique used is qualitative content analysis, involving the grouping, categorization, and synthesis of various findings from the literature to formulate a theoretical understanding of contemporary issues in Islamic education. The findings reveal that Islamic education curricula remain overly theoretical and lack integration with practical skills relevant to the labor market, resulting in graduates who struggle to compete in the workforce. Additionally, disparities in access to education between urban and rural areas are evident, driven by differences in infrastructure, distribution of qualified educators, and access to educational technology. The limited innovation in utilizing technology within Islamic educational institutions further hinders the effectiveness of learning and the readiness of graduates to face the demands of Industry 4.0. The novelty of this research lies in its identification of strategic solutions such as skill-based curriculum reform, equitable access to education, and optimal use of digital technology to enhance the competitiveness of Islamic education graduates.